Persistent systemic inflammation in unstable angina is largely unrelated to the atherothrombotic burden. - Monaco, C; Rossi, E; Milazzo, D; Citterio, F; Ginnetti, F; D'Onofrio, G; Cianflone, D; Crea, F; Biasucci, L; Maseri, A (2005)
OBJECTIVES: The aim of this study was to assess the relationship between systemic inflammation, atherosclerosis, and thrombosis in two distinct clinical models of atherothrombosis. BACKGROUND: Persistent unstable angina (UA) is commonly associated with coronary thrombosis and persistent systemic inflammation. METHODS: We assessed circulating markers of activation of the thrombotic and fibrinolytic cascades and systemic soluble and cellular markers of inflammation on admission in 40 patients with persisting UA (Braunwald class IIIB; group 1) and 30 patients with Leriche-Fontaine stage IIB-III peripheral artery disease awaiting revascularization (group 2). RESULTS: The extent of atherosclerosis (p < 0.01) and activation of the coagulation system were greater in group 2, which had higher thrombin-antithrombin III complexes and D-dimer levels (2.7 and 24.4 microg/l, respectively), than in group 1 (2.0 microg/l and 12.9 microg/l, p = 0.02 and p = 0.0001, respectively). In contrast, C-reactive protein and interleukin-6 levels were higher in group 1 (7.6 pg/ml and 7.8 pg/ml, respectively) than in group 2 (4.5 pg/ml and 3.0 pg/ml, p < 0.01 and p = 0.03, respectively). Moreover, neutrophil activation was only found in group 1 (neutrophil myeloperoxidase content -4.0 arbitrary units vs. +3.4 arbitrary units in group 2, p < 0.0001). These differences persisted during the initial three days of hospitalization. CONCLUSIONS: Such a large, consistent discrepancy between atherothrombotic burden and systemic inflammation suggests that atherothrombosis, by itself, is an unlikely cause of persisting, recurring UA. An understanding of the primary inflammatory mechanisms of persistent and recurrent coronary instability could open the way to novel therapeutic strategies.